THE RELATIONSHIP MODEL OF FEAR OF COVID-19, TRAVEL ANXIETY, AND RISK ATTITUDE TOWARD TRAVEL INTENTION IN THE NEW NORMAL ERA: A STUDY OF MARINE TOURISM IN THE EASTERN SALIENT OF JAVA, INDONESIA - Verinita, Verinita; Suryaningsih, Ika Barokah; Pratama, Mohamad Dito; Susanto, Arnis Budi (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
The COVID-19 pandemic had influenced the global economy, including Indonesia